Back Cover: Total Synthesis of Calophyline A (Angew. Chem. Int. Ed. 35/2016). Issue 35 (30th June 2016) - Li, Guang; Xie, Xiaoni; Zu, Liansuo
Abstract : Skeletal rearrangements represent a fascinating approach for generating complex architectures. In their Communication onpage 10483 ff., L. Zu and co‐workers report the first total synthesis of calophyline A, by employing an aza‐pinacol rearrangement as the key strategy.